Prevalence and causes of vision loss in East Asia in 2015: magnitude, temporal trends and projections. Issue 5 (28th August 2019) - Cheng, Ching-Yu; Wang, Ningli; Wong, Tien Y; Congdon, Nathan; He, Mingguang; Wang, Ya Xing; Braithwaite, Tasanee; Casson, Robert J; Cicinelli, Maria Vittoria; Das, Aditi; Flaxman, Seth R; Jonas, Jost B; et al.
Abstract : Background: To determine the prevalence and causes of blindness and vision impairment (VI) in East Asia in 2015 and to forecast the trend to 2020. Methods: Through a systematic literature review and meta-analysis, we estimated prevalence of blindness (presenting visual acuity <3/60 in the better eye), moderate-to-severe vision impairment (MSVI; 3/60≤presenting visual acuity <6/18), mild vision impairment (mild VI: 6/18≤presenting visual acuity <6/12) and uncorrected presbyopia for 1990, 2010, 2015 and 2020. A total of 44 population-based studies were included. Results: In 2015, age-standardised prevalence of blindness, MSVI, mild VI and uncorrected presbyopia was 0.37% (80% uncertainty interval (UI) 0.12%–0.68%), 3.06% (80% UI 1.35%–5.16%) and 2.65% (80% UI 0.92%–4.91%), 32.91% (80% UI 18.72%–48.47%), respectively, in East Asia. Cataract was the leading cause of blindness (43.6%), followed by uncorrected refractive error (12.9%), glaucoma, age-related macular degeneration, corneal diseases, trachoma and diabetic retinopathy (DR). The leading cause for MSVI was uncorrected refractive error, followed by cataract, age-related macular degeneration, glaucoma, corneal disease, trachoma and DR. The burden of VI due to uncorrected refractive error, cataracts, glaucoma and DR has continued to rise over the decades reported. Conclusions: Addressing the public healthcare barriers for cataract and uncorrected refractive error can help eliminate almost 57% of all blindness cases in this region. Therefore, public healthcare efforts should be focused on effective screening and effective patient education, with access to high-quality healthcare.